Photoswitchable phosphines in catalysis. Issue 22 (25th September 2020) - Medici, Fabrizio; Goual, Nawel; Delattre, Vincent; Voituriez, Arnaud; Marinetti, Angela
Abstract: Photoswitchable catalysts based on phosphorus ligands have been overlooked so far, despite the growing current interest for catalysts control through external stimuli. This review surveys the current knowledge in the field, including synthetic approaches to photoswitchable phosphines and their transition metal complexes, and applications in rhodium, palladium, gold, ruthenium and copper catalysis. This survey demonstrates that both regulation of the catalytic activity and tuning of the chemo‐ and enantioselectivity can be achieved using irradiation as a non‐invasive external stimulus. Non‐catalytic uses of photoswitchable phosphines in organic synthesis are also mentioned. Abstract : Photoswitchable phosphines : The spatio‐temporal control of catalytic processes through external stimuli is currently pursued notably by means of photoresponsive phosphorus ligands. This minireview illustrates this field by summarizing the state of art in the design of azobenzene, dithienylethene and biindane‐derived trivalent phosphines. Examples of photoswitch effects on the catalytic activity, regioselectivty and enantioselectivity are outlined.